2006
DOI: 10.1007/s10509-006-0954-3
|View full text |Cite
|
Sign up to set email alerts
|

On Plane Symmetric Domain Walls and Cosmic Strings in Bimetric Theory

Abstract: Plane symmetric thick domain walls and cosmic strings are considered in Rosen's (General Relativity and Gravitation 4, 435, 1973) bimetric theory of gravitation. It is shown that, in this theory, thick domain walls and cosmic strings do not exist. Hence, the vacuum solutions in both the cases are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Recently, Reddy et al [17] have shown the non-existence of plane symmetric domain walls and cosmic strings in Rosen's [19] bimetric theory of gravitation. Here we have shown that axially symmetric thick domain walls and cosmic strings do not survive in Rosen's bimetric theory of gravitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Reddy et al [17] have shown the non-existence of plane symmetric domain walls and cosmic strings in Rosen's [19] bimetric theory of gravitation. Here we have shown that axially symmetric thick domain walls and cosmic strings do not survive in Rosen's bimetric theory of gravitation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular Mohanty et al [9] and Mohanty and Sahoo [8] have shown the non-existence of perfect fluid or mesonic perfect fluid models in bimetric theory while Reddy [15] has established the non-existence of Bianchi type string cosmologies in this theory. Recently, Reddy et al [17] have shown that plane symmetric domain walls and cosmic strings do not exist in bimetric theory. Inspite of the fact that a lot of work has been done, in this direction, it is evident from literature that there is need for further investigation which may unravel some of the hidden secrets of the theory.…”
Section: Introductionmentioning
confidence: 99%
“…It also becomes important when some types of the topological effects are needed suddenly by assigning an independent metric. In the context of modified theories of gravity, cosmic strings are investigated in f (R) gravity [58,60], teleparallel theories [61][62][63], brane worlds [64], Kaluza-Klein models [65], Lovelock Lagrangians [66], Gauss-Bonnet [67][68][69], Born-Infeld [70,71], bimetric theories [72], non-relativistic models of gravity [73], scalar-tensor theories [74][75][76][77][78][79], Brans-Dicke theory [80][81][82][83][84][85], dilation gravity [86,87], non-minimally coupled models of gravity [88], Mimetic gravity [89] and, recently, in the Bose-Einstein condensate strings [90]. However, the cosmic string is still unexplored in gravity's rainbow setting.…”
mentioning
confidence: 99%
“…Reddy et al [26] have established the non-existence of axially symmetric cosmological model with domain walls and cosmic string. Sahoo [27] has shown that the spherically symmetric cosmological model did not exist in Rosen's bimetric theory of gravitation when the source of gravitation was either perfect fluid or massive string whereas the model did exist in scalar meson field.…”
Section: S D Katore R S Rane and K S Wankhadementioning
confidence: 99%